4.REPRODUCTIVE HORMONAL ASSAY OF A SAMPLE OF IRAQI OBESE MALES (Iraqi Journal of Medical Sciences, 2019)
Background:The World Health Organization considered obesity as a medical condition that may lead to reduced life expectancy and/or increased health problems. While much of the focus on the impairments caused by obesity is on somatic health, recent data suggest that reproductive health may also be impacted.Objective:To quantify the relation between obesity and the reproductive hormones.Methods:This cross-sectional study was carried out at nutrition clinic in three teaching hospitals and one obesity clinic in a medical college in Baghdad. The body mass index (BMI) calculation, blood sugar, serum cholesterol, triglyceride, testosterone, prolactin, follicular stimulating hormone (FSH), and luteinizing hormone (LH) were measured.Results:Ninety-five adult obese males participated in this study. Serum testosterone had significant negative correlation with BMI, weight, serum cholesterol, and serum triglyceride while serum LH had significant positive correlation with BMI (p value was 0.013), weight (p value was 0.027), and serum triglyceride (p value was 0.049).Conclusion:Male obesity has significant effect on serum level of testosterone and LH.Keywords:Obesity, reproductive hormonesCitation:Abdul-Rahman IM., Abdul-Ameer AJ. Reproductive hormonal assay of a sample of Iraqi obese males. Iraqi JMS. 2019; 17(2): 114-119. doi: 10.22578/IJMS.17.2.4
Keywords: Obesity; reproductive hormones